The Role of Pelvic Floor Muscles Exercises with Biofeedback as Adjuvant Treatment in Men with Erectile Dysfunction - Guido O Vianney; Ratna D Haryadi; Rwahita Satyawati; Onny P Sono (Indonesian Journal of Physical Medicine & Rehabilitation, 2014)
Objective: To evaluate the efficacy of pelvic floor muscle exercise programs for men with erectile dysfunction problems.Methods: A randomized controlled group designed study. Sixteen men with erectile dysfunction who had undergone pharmacological treatment from the Andrology Clinic and were referred to thePhysical Medicine and Rehabilitation Department Dr. Soetomo Hospital were divided into 2 groups. The first group was treated with pelvic floor muscle exercises for 12 weeks, while the second groupacted as control. The parameters of this study were evaluated in weeks 4, 8 and 12. This consisted of an evaluation of pelvic floor muscle strength, which was performed by digital anal assessment, and pressurebiofeedback Myomed 932. The evaluation of erectile function was based on the IIEF-5 (International Index of Erectile Function – 5) questionnaire and the EHS (Erectile Hardness Score).Results: An increase in the maximum contraction of pelvic floor muscles was seen in the intervention group after 8 weeks of treatment (p=0.011). Six subjects in the intervention group (75%) gained anormal anal strength based on digital anal assessment at the end of study. The IIEF-5 score of the intervention group improved after 8 weeks of treatment (p=0.012). Threesubjects (37.5%) in the intervention group got a maximum hardness score and 4 subjects (50%) gained an improvement of the hardness score.Conclusion: Comparing of the results of the protocol reported here shows that pelvic floor muscle exercises improve erectile function in men with erectile dysfunction problems.Keywords: pelvic floor muscle exercises, biofeedback, erectile dysfunction